Uma análise relacional sistêmica do contexto de famílias com filhos diagnosticados com transtorno do espectro do autismo e sua rede social - Santos, Ricardo (2020)
In its trajectory, the family with a child diagnosed with ASD faces challenges related to multiple life contexts, among them the integration between them. This study aimed to investigate and understand the experiences of families with children diagnosed with ASD, focusing on parent-child relational processes, and the family with broader socio-cultural systems. Study supported by the Postmodern paradigm of science on the knowledge of reality as a used construction. An analysis was guided by the epistemological assumptions of postmodern approaches, highlighting the Systemic Family Therapy and the practices of Dialogic and Narrative therapies, which shifts the focus from an essentialist understanding based on deficits, to a social narrative of the self and to socially constructed realities, contributing to the understanding that resources and relational skills present in the interrelationships of children diagnosed with ASD constitute a vast field of study. Exploratory study, whose methodology generates rich descriptions, people‟s actions and contexts, emphasizing personal experiences, specific situations and local knowledge. The literature on “Family and Autism” was vastly revised, enabling the deconstruction of naturalized conceptions about the relational context of families with children with ASD. Four families took part, with at least one four-year-old child diagnosed with ASD. A semi-structured dialogic interview was used, favoring the emergence of narratives from the participant's life experiences. It was opted for Discourse Analysis, maintaining the framework of a postmodern epistemology that understands interview as an action, through which versions of reality are constructed. The results suggested that normative conceptions tend to interfere in the process of recognition of the child's expression, and showed the importance of language constructed according to the meanings that individuals attribute to their experiences. Observations and reflections that occurred reinforced the position that one can aspire for a better standing of these children in the world, not only by the dialogue between the knowledge, but also by the belief in the potential knowledge of those involved